Pengembangan Perangkat Model Blended Learning untuk Meningkatkan Efektivitas Penerapan Pendidikan Jarak Jauh di SMKN 2 Gerung - Muzakkir Muzakkir; Restu Wibawa; Fitri Astutik; Muhakkikin Muhakkikin (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2018)
Abstract: This study aims to develop a set of blended learning models to improve the effectiveness of theapplication of a long distance education in SMK 2 Gerung. This research used research and development (R & D). This research developed learning tools that support the effectiveness of the blended learning application. The tools to be developed were modules, syllabus, learning implementation plans and guidebooks for Schoology use. Product development process was done through the stages of defining, designing and developing after being tested. The design of this study was only one group for the implementation of product testing. The research was conducted in Class X of SMK 2 Gerung West Lombok. Based on the results of students learning data, it was obtained asymp values. Sig = 0.000 which means smaller than <0.05. So, it can be concluded that there is a difference between students learning outcomes of pretest and posttest which means that the blended learning model can increase the effectiveness of long distance education. The mastery of the standard score of learning outcomes for posttest scores = 84 from the value of the standard score 72 and the percentage of students who complete up to 80%. Based on the responses of students, it was found as much as 80% of students who answered the criteria of Strongly Agree (ST). From these results, the tools of the blended learning model can support the effectiveness of the implementation of long distance education. Abstrak: Penelitian ini bertujuan untuk mengembangkan perangkat model blended learning untukmeningkatkan efektivitas penerapan pendidikan jarak jauh di SMKN 2 Gerung. Penelitian ini termasuk jenis reaserch and development (R&D). Melalui penelitian ini akan mengembangkan perangkat pembelajaran yang mendukung efektivitas penerapan blended learning. Perangkat yang akan dikembangkan berupa modul, silabus, rencana pelaksanaan pembelajaran dan buku panduan pemanfaatan Schoology. Proses pengembangan produk melalui tahap pendefinisian (define), perancangan (design), dan pengembangan (develop) setelah itu diuji coba. Desain penelitian ini hanya satu kelompok untuk pelaksanaan uji produk. Penelitian dilaksanakan di Kelas X SMKN 2 Gerung Lombok Barat. Berdasarkan olah data hasil belajar siswa diperoleh nilai Asymp.Sig = 0.000 artinya lebih kecil dari < 0.05. Sehingga dapat disimpulkan bahwa ada perbedaan antara hasil belajar siswa untuk pretest dan postest artinya perangkat model blended learning dapat meningkatkan efektivitas pendidikan jarak jauh. Ketuntasan hasil belajar rata-rata nilai postest = 84 dari nilai KMM 72 dan presentase siswa yang tuntas 80%. Berdasarkan respon siswa sebanyak 80% siswa yang menjawab pada kriteria SangatSetuju (ST). Dari hasil tersebut bahwa perangkat model blended learning dapat menunjang efektivitaspelaksanaan pendidikan jarak jauh.